IMPLEMENTATION OF COMMUNICATION STRATEGIES IN SPORTS NEWSPAPER AND JOURNALISTIC DISCOURSE - S. Egorova; M. Laskova (Гуманитарные и юридические исследования)
He communicative strategies used in sports newspaper and journalistic discourse have not been studied enough: the communication strategy is one of the most relevant aspects of the study in the field of discourse theory, first of all, because thanks to the implementation of communication strategies, the author's intentions are embodied, acquire their ontological status as the goals of communication. The study of any kind of discourse in the communicative-pragmatic aspect would be incomplete and would not have sufficient explanatory power without resorting to the concept of a communicative strategy. A communicative strategy in the form in which it is implemented in any discourse can be considered as a complex of speech actions that are aimed at achieving communicative goal. Modern linguistics has a number of definitions of communicative strategy and concepts for the implementation of communicative strategies and tactics in discourse and text. In the process of communicative strategy implementation, speech impact on the addressee is performed in such a way as to transform his behavior to a certain extent in accordance with the goals of the addressee. In this regard, it is necessary to emphasize that the addressee plans communicative act in accordance with his goals and objectives, ensuring the success of his communicative efforts. M. L. Makarov pays special attention to linguistic means, but not to the goals of the communication act, which allows us to speak about a certain convergence of communicative strategy definition in its interpretation with communicative tactics, because the means of speech and language are precisely aimed at certain communication strategy forming. According to T. A. van Dijk, communication strategy is the most general instruction "for each specific situation of interpretation" [7], with the help of communication strategy, both the individual goals of the addressee and some goals that are significant for society can be achieved. The choice of a specific communication strategy is determined, according to T. A. van Dijk, the specific intention of the addressee, which is necessarily manifested in given communicative situation, which allows us to correlate such concept with a cognitive-discursive approach that is significant for modern linguistics.